Identifying knowledge needed to improve surgical care in Southern Africa using a theory of change approach. Issue 6 (15th June 2021) - Breedt, Danyca Shadé; Odland, Maria Lisa; Bakanisi, Balisi; Clune, Edward; Makgasa, Moneimang; Tarpley, John; Tarpley, Margaret; Munyika, Akutu; Sheehama, Jacob; Shivera, Theresia; Biccard, Bruce; Boden, Regan; et al.
Abstract : Surgical healthcare has been prioritised in the Southern African Development Community (SADC), a regional intergovernmental entity promoting equitable and sustainable economic growth and socioeconomic development. However, challenges remain in translating political prioritisation into effective and equitable surgical healthcare. The AfroSurg Collaborative (AfroSurg) includes clinicians, public health professionals and social scientists from six SADC countries; it was created to identify context-specific, critical areas where research is needed to inform evidence-grounded policy and implementation. In January 2020, 38 AfroSurg members participated in a theory of change (ToC) workshop to agree on a vision: 'An African-led, regional network to enable evidence-based, context-specific, safe surgical care, which is accessible, timely, and affordable for all, capturing the spirit of Ubuntu[1] ' and to identify necessary policy and service-delivery knowledge needs to achieve this vision. A unified ToC map was created, and a Delphi survey was conducted to rank the top five priority knowledge needs. In total, 45 knowledge needs were identified; the top five priority areas included (1) mapping of available surgical services, resources and providers; (2) quantifying the burden of surgical disease; (3) identifying the appropriate number of trainees; (4) identifying the type of information that should be collected to inform service planning; and (5) identifying effective strategies that encourage geographical retention of practitioners. Of the top five knowledge needs, four were policy-related, suggesting a dearth of much-needed information to develop regional, evidenced-based surgical policies. The findings from this workshop provide a roadmap to drive locally led research and create a collaborative network for implementing research and interventions. This process could inform discussions in other low-resource settings and enable more evidenced-based surgical policy and service delivery across the SADC countries and beyond.